2010
DOI: 10.1002/ijc.24907
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking, environmental tobacco smoke exposure and pancreatic cancer risk in the European Prospective Investigation into Cancer and Nutrition

Abstract: Cigarette smoking is an established risk factor for pancreatic cancer. However, prospective data for most European countries are lacking, and epidemiologic studies on exposure to environmental tobacco smoke (ETS) in relation to pancreatic cancer risk are scarce. We examined the association of cigarette smoking and exposure to ETS with pancreatic cancer risk within the European Prospective Investigation into Cancer and Nutrition (EPIC). This analysis was based on 465,910 participants, including 524 first incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
93
3
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 135 publications
(117 citation statements)
references
References 31 publications
15
93
3
6
Order By: Relevance
“…5 Active and moderately active according to the Cambridge Physical Activity Index incorporates occupational and nonoccupational physical activity. 6 Pill, hormone replacement therapy and estrogen replacement therapy. 7 Missing data of 60 cases and 61 controls.…”
Section: Serum One-carbon Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Active and moderately active according to the Cambridge Physical Activity Index incorporates occupational and nonoccupational physical activity. 6 Pill, hormone replacement therapy and estrogen replacement therapy. 7 Missing data of 60 cases and 61 controls.…”
Section: Serum One-carbon Metabolitesmentioning
confidence: 99%
“…2 Because pancreatic cancer is most often diagnosed at a late stage, prognosis is poor with 1-year survival rates of 20% and 5-year survival rates of only 4-5%. 2,3 Several risk factors have been consistently associated with the risk of developing pancreatic cancer, including family history of pancreatic cancer, 4 chronic pancreatitis, 5 cigarette smoking, 6 diabetes mellitus 7 and obesity. 8 According to the 2012 WCRF/AIRC expert report, evidence for the relation between vegetable and fruit consumption and pancreatic cancer risk is limited and inconsistent, 9 with inverse associations found in case-control studies and no associations found in cohort studies.…”
mentioning
confidence: 99%
“…Most studies, including several cohort studies, a meta-analysis, and a pooled analysis of eight cohorts, indicated that current smokers had about a 2-fold increased pancreatic cancer risk compared with never smokers (2)(3)(4)(5)(6). Former smokers experience lower increased risks of pancreatic cancer as compared with current smokers, with risks ranging from 1.1 to 1.6 (2,(7)(8)(9)(10)(11). Pancreatic cancer risk increases with both number of cigarettes smoked daily (3,(5)(6)(7)(8)12) and duration of smoking (3,5,8,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Former smokers experience lower increased risks of pancreatic cancer as compared with current smokers, with risks ranging from 1.1 to 1.6 (2,(7)(8)(9)(10)(11). Pancreatic cancer risk increases with both number of cigarettes smoked daily (3,(5)(6)(7)(8)12) and duration of smoking (3,5,8,10,11). After quitting cigarette smoking, the risk decreases gradually within 10 to 15 years towards unity (5,8,12,13).…”
Section: Introductionmentioning
confidence: 99%
“…The water pipe smoker may, therefore, inhale the equivalent of 100 or more cigarettes. [8][9][10] Consequently, we firmly believe that WPS is an important risk factor in the development of several human cancers, especially pancreatic cancer according to the study of Vrieling et al 1 Meanwhile, we propose, to conduct an international epidemiological study, in collaboration with several national Cancer centers, regarding the risk factor of WPS in human pancreatic cancer as well as other human cancers.…”
Section: Dear Editormentioning
confidence: 99%